Opportunities to increase whole grain intake within the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). Issue 2 (13th October 2022) - Slavin, Joanne L.; Sanders, Lisa M.; Stallings, Virginia A.
Abstract: Background : In 2017, the National Academies of Science, Engineering, and Medicine, at the request of the United States Department of Agriculture Food and Nutrition Service (USDA FNS), published an expert report proposing updates to food packages for the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). Recommendations included adoption of the "whole grain‐rich" criteria instead of the whole grain health claim to classify whole grain breakfast cereals, and further, that all breakfast cereals be whole grain‐rich. Aims & Methods : To discuss the advantages and implications of these recommendations, the Cereal & Grains Association, in partnership with General Mills, Inc., convened an expert roundtable in April 2022. Results & Discussion : The roundtable agreed increasing whole grain intake among WIC participants is critical and adoption of the whole grain‐rich criteria aligns with the 2020 Dietary Guidelines for Americans and child nutrition programs. However, potential challenges in requiring all cereals to be whole grain‐rich, including cost, and consumer choices based on taste and cultural preferences were noted and potential solutions discussed. Conclusion : Considering the public health need to increase whole grain intake, USDA FNS should increase the provision of whole grain in WIC food packages, while also considering the preferences of WIC participants and food costs.